INCLUSIVE DEVELOPMENT: An Indian Theological Response - INDIAN THEOLOGICAL ASSOCIATION (Asian Horizons, 2014)
We, the 55 participants of the 36th National Conference and Annual Meeting of the Indian Theological Association (ITA), gathered together at Proggaloy, Archdiocesan Pastoral Centre, Archdiocese of Kolkata, Basarat, Rathtala, Kolkata, from 02 – 06 October 2013, deem it a matter of importance to bring out this statement which contains the fruits of our reflection and deliberation during the conference.